Pengaruh Literasi Keuangan, Financial Education, Status Sosial Ekonomi dan Gaya Hidup Terhadap Manajemen Keuangan Pribadi pada Generasi Z Kota Pekanbaru - Saptina Norfadila; Umi Rachmah Damayanti (Al-Manar Journal of Accountancy and Business Studies, 2025)
This research is motivated by the consumerist tendencies of Generation Z, which cause them to struggle in managing their personal finances. The purpose of this study is to examine the influence of financial literacy, financial education, socioeconomic status, and lifestyle on personal financial management among Generation Z in Pekanbaru City. The focus population in this quantitative analysis is the 169,276 Generation Z individuals aged 17-27 years in Pekanbaru City. The sample was determined using purposive sampling and quota sampling techniques, with a total of 210 respondents. The data sources used in this research include both primary and secondary data. The findings of this study indicate that financial literacy, financial education, and socioeconomic status have a positive and significant influence on personal financial management. Conversely, lifestyle has a negative influence on the personal financial management of Generation Z in Pekanbaru City. The R Square value of 0.584 or 58.4% suggests that the dependent variable in this study is influenced by financial literacy, financial education, socioeconomic status, and lifestyle, while the remaining 41.6% is influenced by other variables not included in this study.